Long-term survival of patients aged 80 years or older treated with radical prostatectomy for prostate cancer. Issue 8 (August 2017) - Dell'Oglio, P.; Zaffuto, E.; Boehm, K.; Trudeau, V.; Larcher, A.; Tian, Z.; Moschini, M.; Shariat, S.F.; Graefen, M.; Saad, F.; Capitanio, U.; Briganti, A.; et al.
Abstract: Background: Radical prostatectomy (RP) is the gold standard for clinically localized prostate cancer (PCa) patients with life expectancy (LE) of at least 10 years. We examined long-term survival of men aged 80 years or older treated with RP and we attempted to identify criteria based on age and comorbidities that could predict survival of at least 10 years after RP, to identify those that might be considered for RP. Patients and methods: In Surveillance Epidemiology and End Results (SEER)-Medicare-linked database, we identified 234 octo- and nonagenarians with clinical T1, T2 or T3 PCa treated with RP between 1991 and 2009. Kaplan–Meier analyses examined 10-year survival patterns. Multivariable Cox regression analyses focused on the combined effect of age and/or Charlson Comorbidity Index (CCI) after adjusting for different confounders. Results: The 10-year overall survival (OS) and cancer specific mortality (CSM) rates in the overall population were 51 and 9.9%. In individuals aged 80–81 years old, the 10-year OS was 62.4 vs. 39.6% in older patients (p = 0.001). Moreover, combination of age 80–81 with CCI = 0 yielded 10-year OS of 67.9 vs. 28.5% in older and sicker patients (p < 0.001). Age 80–81, absence of comorbidities and the combination of age 80–81 with CCI = 0, represented independent predictors of lower overall mortality (all p ≤ 0.01). Conclusions: Two out of three individuals selected for RP aged 80–81 years and without comorbidities, fulfill the criterion of LE of 10 years or more. Therefore, elderly PCa individuals can be suitable for surgical management, if appropriately selected, based on LE criterion.